Improvement of Science Learning Achievement in Animal and Plant Material in My Home Environment in SDN Karanggintung 07 - Rotiah Rotiah (Universitas Sebelas Maret, 2020)
This study aims to describe efforts to improve science learning achievement through the use of IT-based learning media (technology science) in grade IV students, to improve science learning achievement through the use of IT-based learning media (Technology Science) in grade IV SDN Karanggintung 07. This research uses based media. IT (Science of Technology) and consists of four stages, namely planning, implementing, observing, and reflecting. The subjects of this study were 18 grade IV students at SDN Karanggintung 07. Data collection techniques used observation sheets and written tests. The results of this study showed A significant increase was seen in the pre-cycle value of students who reached KKM only 50%, after cycle 1 increased to 55.55%, cycle II 66.66% and the peak in cycle III reached 83.33%. Thus the use of IT-based media (Technology Science) can improve the learning achievement of fourth grade students in science subjects animal and tumb God in my neighborhood.